2011
DOI: 10.1074/jbc.m110.176636
|View full text |Cite
|
Sign up to set email alerts
|

Non-B DNA-forming Sequences and WRN Deficiency Independently Increase the Frequency of Base Substitution in Human Cells

Abstract: Although alternative DNA secondary structures (non-B DNA) can induce genomic rearrangements, their associated mutational spectra remain largely unknown. The helicase activity of WRN, which is absent in the human progeroid Werner syndrome, is thought to counteract this genomic instability. We determined non-B DNA-induced mutation frequencies and spectra in human U2OS osteosarcoma cells and assessed the role of WRN in isogenic knockdown (WRN-KD) cells using a supF gene mutation reporter system flanked by triplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 70 publications
1
43
1
Order By: Relevance
“…Several repetitive elements were found in the vicinity of these juxtaposed mutations: for example, an inverted repeat and a symmetric element were found in the vicinity of the c.1177-8 mutations; a direct repeat and run of identical nucleotides span the site of the c.5894 mutations, whereas c.6409 occurs in the vicinity of symmetric elements. These repeat sequences may serve to facilitate the formation of multiple non-B DNA structures, 48 thereby accounting for the hypermutability of these sites (shaded tumour IDs in Table 1). Previous mutation studies have also purportedly found evidence for potential clustering of mutations identified in separate neurofibromas from the same patient, 48,49 but such conclusions have never before received formal statistical support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several repetitive elements were found in the vicinity of these juxtaposed mutations: for example, an inverted repeat and a symmetric element were found in the vicinity of the c.1177-8 mutations; a direct repeat and run of identical nucleotides span the site of the c.5894 mutations, whereas c.6409 occurs in the vicinity of symmetric elements. These repeat sequences may serve to facilitate the formation of multiple non-B DNA structures, 48 thereby accounting for the hypermutability of these sites (shaded tumour IDs in Table 1). Previous mutation studies have also purportedly found evidence for potential clustering of mutations identified in separate neurofibromas from the same patient, 48,49 but such conclusions have never before received formal statistical support.…”
Section: Discussionmentioning
confidence: 99%
“…These repeat sequences may serve to facilitate the formation of multiple non-B DNA structures, 48 thereby accounting for the hypermutability of these sites (shaded tumour IDs in Table 1). Previous mutation studies have also purportedly found evidence for potential clustering of mutations identified in separate neurofibromas from the same patient, 48,49 but such conclusions have never before received formal statistical support. Although it is possible that the germline NF1 mutation might influence the location of subsequent somatic NF1 mutations, our current study on a relatively small number of paired germline somatic mutations have provided no evidence to support this postulate.…”
Section: Discussionmentioning
confidence: 99%
“…We show that, unlike wild-type cells, cells that lack WRN exhibit a 5-fold elevated mutation frequency during extension of synthetic DNA substrates in vivo. Using a completely different reporter assay, Bacolla et al (43) also recently noted that WRN deficiency increases the frequency of base substitution errors 2-fold in human cells. This spontaneous increase in mutation frequency may be low, but it is observed in unstressed cells that are proficient for Pol ␦ and ⑀ proofreading.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, without a functional RecQ helicase, DNA replication does not advance normally. In humans, lacking of WRN or BLM protein accumulates aberrant replication intermediates (Harrigan et al, 2003;Cheok et al, 2005), this may allow for certain non-B DNA structure forming (Mohaghegh et al, 2001;Bacolla et al, 2011). Therefore, it is not surprising to see that more and more reports are going to be published www.intechopen.com…”
Section: Recq Helicases Blm Wrn Recql4 and Sgs1mentioning
confidence: 99%